West Papuan Teachers’ Perceptions on Translanguaging Practices in EFL Classroom Interaction - Rahmawansyah Sahib; Najiba Nawing; Hamra Sari; Syamsir bin Ukka (Universitas Lancang Kuning, 2020)
The belief that the West Papuan teachers applied translanguaging practice as strategy to enhance their students in ELT classroom. This study, investigated the West Papuan EFL teachers’ perceptions on translanguaging practices. It focused to explore the teachers’ knowledge and the teachers’ experience on translanguaging practice in EFL Classroom interaction in West Papuan. The participants of the study were three English language teachers (EFL) who work at state Islamic junior high school of Manokwari in West Papuan. The utterances of teachers’ interview were analyzed descriptive qualitatively using discourse analysis and the data gathered from classroom observations and semi-structured interviews were exposed to structural-coding analysis. The results showed that the EFL teachers have some perceptions about knowledge on translanguaging practice. There were translanguaging is a combination of Indonesian and English in the ELT Classroom, Translanguaging is a material transfer tool, Translanguaging is a safe and productive zone for students to do communication, Translanguaging is the moment for using mother tongue and local language in explaining material, Translanguaging is a strategy to improve and facilitate the understanding of material, Translanguaging is a strategy to enliven the classroom atmosphere. The EFL teachers also have experiences to apply translanguaging practice in ELT classroom. They used translanguaging to appreciate students in process of asking and answer the questions, to facilitate the transfer of material toward students, to assist the students in apply the target language, to respect the students’ questions that use the local language, and translanguaging as a challenge for teachers to master the local language of students.